Pengaruh Pijat Endorphin Terhadap Lama Kala I Pada Ibu Bersalin - Sukarsih, Rachmawati Ika (Universitas Muhammadiyah Surabaya, 2020)
Objective: Labor is a physiological thing experienced by everyone, but it can also become pathological with prolonged labour. One of the efforts to reduce the risk of prolonged labour is by doing endorphin massage in maternity mothers. This study aimed to determine the effect of endorphin massage on the length of the first stage of labour.Â Methods: This research was conducted at TPMB Siti Alfiyah. The population in this study were all mothers who gave birth at TPMB Siti Alfiyah from February to June 2019 using a purposive sampling technique with predetermined inclusion and exclusion criteria. The number of samples in this study was 28 respondents. This type of research is a cross-sectional approach. This study uses an observation sheet research instrument seen from medical records. The type of data in this study is secondary data obtained or collected through medical records. The data analysis technique used is univariate and bivariate analysis.Â Results: Most mothers are 26-35 years old, and as many as 14 respondents (50.0%). Most of the parity of multiparous mothers was 17 respondents (60.7%). The duration of labour in the active phase of the first stage of labour women who received endorphin massage experienced the majority of labour durations being faster than the theory, as many as 18 respondents (64.3%).Â Conclusion: This study concludes that the maternity mothers who received endorphin massage were the majority of the duration of the first stage of labour in the active phase faster than the theory. Maternity mothers, husbands, and families can apply endorphin massage since gestational age > 36 weeks to shorten the length of time for delivery and to provide a sense of calm and comfort before the delivery process.